Verba vana? A note on Arm. zowr ‘vain’ and zroyc‘ ‘talk’ (Atti del Sodalizio Glottologico Milanese, 2024)
It is argued that Arm. zowr ‘vain’ is the derivational basis of zroyc‘ ‘talk’ with a semantic shift from ‘idle talk’ to ‘talk’. -oyc‘ may be a case-form of a decasuative derivative of the underlying nominal zowr, i.e., *zroy → *zroyk‘, zroyc‘.